MASJID, HALAQOH DAN ISLAMIC ACTIVISM Potret Halaqoh di Masjid-masjid Kota Surakarta - Fathol Hedi (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
The Islamic activism movement in the Surakarta and surrounding areas is metamorphosis by forming (new community) in the local political level in the form of recitation or small halaqoh in the mosque as a form of cadre processing. From these small halaqoh then they established educational institutions, non profit charity institutions, and media procurement,that is intended for the ideologization business by forming a small community known as the laskar or front which drives of Islamic activism group in Surakarta and its surrounding. From that statement, the research about their on models and networks of halaqoh is important tobe studied.This research was descriptive qualitative research, the data collection is done through three ways: direct observation in a mosque halaqoh based on a radical understanding in Surakarta, in-depth interviews on their halaqoh network, and documentation. The data analysis technique was an interactive analysis model, including three stages: data reduction, data display; and drawing conclusions. The obtained conclusion will be verified by its truth and validity by two ways, they are triangulation of data; and review of informants.Halaqoh reviewed from social movements requires a group of people to reject or accept the value in a organized way. With this model, the mosque becomes the basis for their regeneration it also has a signifcant role, to accelerate the spread of Islamic-ideology in the society. The overwhelming halaqoh held in some mosques in Surakarta, such as Jami 'MUI, Marwah Nurul Huda UNS and Sampangan, principally utilize the open political structure of post-reforms in 1998. According to Resources Mobilization of Theory-the overflow of resources in every mosque, network, economic access, and so on can carry out the encouraging the society or the congregation to have power, capability, potential to make alteration. In the framing of the discourse, halaqoh of Islamic activism such as Jami 'MUI and Nurul Huda mosque massively produce the discourse through various media so that the discourse is reportedly gotten by the lower society. The Framing could be in the form of halaqoh, recitation, Friday sermon, newsletter, or through the social media such as facebook and live streaming TV, they already have this all.